A Bibliometric Analysis of Research on Depression and Exercise in Older Adults - Canan Yüksel Haji; Emine Nacar; Sinem Suner-Keklik (European Journal of Multidisciplinary Health Sciences, 2026)
Depression is a common mental disorder worldwide and significantly affects older adults. Considering the potential role of exercise in depression management, examining research trends in this field using bibliometric methods is important. Accordingly, this study aimed to provide a systematic overview of the development of the literature by analysing English-language publications indexed in the Web of Science Core Collection using search terms related to depression, exercise, and older adults, without applying publication-year restrictions.A total of 53 publications identified through the search conducted on 1 March 2026 were analysed using Biblioshiny and VOSviewer. The earliest publication on depression and exercise in older adults was published in 2007, and publication output fluctuated over time. The highest numbers of publications were recorded in 2010 and 2021. A total of 421 authors contributed to the publications, and the average number of citations per publication was 57.11. The most productive journals were the American Journal of Geriatric Psychiatry, the Journal of Affective Disorders, and Aging & Mental Health. Based on local citation counts, the most highly cited study was “Effects of Exercise on Electroencephalographic Mean Frequency in Depressed Elderly Subjects,” published by Silveira et al. in 2010. The USA and England ranked highest in publication output, whereas the USA and Germany ranked highest in citation counts. The most productive institutions were King’s College London and the University of Genoa, while the most prominent authors were Amore M., Murri M.B., and Zanetidou S. The most frequently used keywords were “depression,” “physical activity,” “exercise,” “geriatric,” and “aerobic exercise.”In conclusion, scientific output on exercise in the management of depression in older adults has generally increased and developed across several disciplines. Further research involving broader international collaboration and more diverse geographical settings is needed.